Altered levels of plasma neuron‐derived exosomes and their cargo proteins characterize acute and chronic mild traumatic brain injury. Issue 4 (3rd January 2019) - Goetzl, Edward J.; Elahi, Fanny M.; Mustapic, Maja; Kapogiannis, Dimitrios; Pryhoda, Moira; Gilmore, Anah; Gorgens, Kimberly A.; Davidson, Bradley; Granholm, Anne‐Charlotte; Ledreux, Aurélie
ABSTRACT: Neuron‐derived exosomes (NDEs) were enriched by anti‐L1CAM antibody immunoabsorption from plasmas of subjects ages 18–26 yr within 1 wk after a sports‐related mild traumatic brain injury (acute mTBI) ( n = 18), 3 mo or longer after the last of 2–4 mTBIs (chronic mTBI) ( n = 14) and with no recent history of TBI (controls) ( n = 21). Plasma concentrations of NDEs, assessed by counts and levels of extracted exosome marker CD81, were significantly depressed by a mean of 45% in acute mTBI ( P < 0.0001), but not chronic mTBI, compared with controls. Mean CD81‐normalized NDE levels of a range of functional brain proteins were significantly abnormal relative to those of controls in acute but not chronic mTBI, including ras‐related small GTPase 10, 73% decrease; annexin VII, 8.8‐fold increase; ubiquitin C‐terminal hydrolase L1, 2.5‐fold increase; AII spectrin fragments, 1.9‐fold increase; claudin‐5, 2.7‐fold increase; sodium‐potassium‐chloride cotransporter‐1, 2.8‐fold increase; aquaporin 4, 8.9‐fold increase (3.6‐fold increase in chronic mTBI); and synaptogyrin‐3, 3.1‐fold increase (1.3‐fold increase in chronic mTBI) (all acute mTBI proteins P < 0.0001). In chronic mTBI, there were elevated CD81‐normalized NDE levels of usually pathologic β‐amyloid peptide 1‐42 (1.6‐fold, P < 0.0001), P‐T181‐tau (2.2‐fold, P < 0.0001), P‐S396‐tau (1.6‐fold, P < 0.01), IL‐6 (16‐fold, P < 0.0001), and prion cellular protein (PRPc) (5.1‐fold, P < 0.0001) with lesser or greater (IL‐6, PRPc) increases in acute mTBI. Increases in NDE levels of most neurofunctional proteins in acute, but not chronic, mTBI, and elevations of most NDE neuropathological proteins in chronic and acute mTBI delineated phase‐specificity. Longitudinal studies of more mTBI subjects may identify biomarkers predictive of and etiologically involved in mTBI‐induced neurodegeneration.—Goetzl, E. J., Elahi, F. M., Mustapic, M., Kapogiannis, D., Pryhoda, M., Gilmore, A., Gorgens, K. A., Davidson, B., Granholm, A.‐C., Ledreux, A. Altered levels of plasma neuron‐derived exosomes and their cargo proteins characterize acute and chronic mild traumatic brain injury. FASEB J. 33, 5082–5088 (2019). www.fasebj.org